Peat soil stabilization using electrokinetic stabilization (EKS) treatment at Parit Lapis Kadir, Batu Pahat, Johor, Malaysia - Wahab, Abdul; Embong, Zaidi; Naseem, Abbas Ali; Ahmad Tajudin, Saiful Azhar; Qamar, Uz Zaman
Peat is found all over the world, which covered about 4.5% of the total world land and considered one of the most challenging soil, it creates many problems in constructions projects due to its characteristics like low shear strength, high water content and high compressibility. Hence, buildings and roads construction on peat has become more complex and differential settlements, slope failures, global instabilities, and long-term excessive settlements have occurred. Developing countries such as Malaysia, also facing such type of problems in building and road constructions. To overcome this problem, several matters related to soft soil strength, its essential to be resolved in proper way. This can be done by performing soil treatment to enhance its strength and physical properties. The application of soil improvement by using the electrokinetic stabilization (EKS) method has the potential to overcome problems such as low shear strength, high moisture content and high compressibility of the low permeable soil. The principles of EKS method involve applying a low potential gradient through electrodes which are inserted in the low permeable soil that cannot readily be drained. The voltage gradient of 110 V and 150 V was applied to the peat soil with the help of aluminium electrodes for the operational period of 3 and 6 hours. The peat sample was collected from Parit Lapis Kadir, Batu Pahat, Johor state, Malaysia. Some soil parameters like shear strength (